2015
DOI: 10.1109/lawp.2014.2365755
|View full text |Cite
|
Sign up to set email alerts
|

A TSVD Analysis of the Impact of Polarization on Microwave Breast Imaging Using an Enclosed Array of Miniaturized Patch Antennas

Abstract: Microwave breast imaging performance is fundamentally dependent on the quality of information contained within the scattering data. We apply a truncated singular-value decomposition (TSVD) method to evaluate the information contained in a simulated scattering scenario wherein a compact, shielded array of miniaturized patch antennas surrounds an anatomically realistic numerical breast phantom. In particular, we investigate the impact of different antenna orientations (and thus polarizations), namely two array c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The problem with the aforementioned cross-correlation based fidelity metric is exposed in its inability to answer the question: how the introduced features impact inversion performance and final image quality. A more advanced method is Truncated Singular Value Decomposition (TSVD) [38], [46]. TSVD method separates the testing of measured data quality from the problem of the inversion algorithm design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem with the aforementioned cross-correlation based fidelity metric is exposed in its inability to answer the question: how the introduced features impact inversion performance and final image quality. A more advanced method is Truncated Singular Value Decomposition (TSVD) [38], [46]. TSVD method separates the testing of measured data quality from the problem of the inversion algorithm design.…”
Section: Resultsmentioning
confidence: 99%
“…Such an antenna would occupy less volume compared to the aforementioned Vivaldi and waveguide antennas [15]. A similar methodology of rectangular geometry is used for designing an array based on the multiband patch antenna [8], [14], [37], [38]. This array successfully fulfills all the aforementioned criteria, In [37], some additional criteria are given, for example possibility of coregistration with Magnetic Resonance Imaging (MRI).…”
Section: A Antenna Design Methodologymentioning
confidence: 99%
“…To improve the matrix condition number, Tikhonov regularization technique was used. Other regularization techniques may also be applied including the Truncated Singular Value Decomposition method . Following Tikhonov's regularization, (7) becomes, true{εk+1true}=true{εktrue}true[JTJ+μRtrue]1true[Jtrue]Ttrue({S}normalmeasFtrue(true{ε0true}true)true[Jtrue](true{εktrue}true{ε0true}true) …”
Section: The Image Reconstruction Algorithmmentioning
confidence: 99%
“…The impact of polarization on image reconstruction was evaluated in Ref. [13], and it was concluded that the effectiveness was limited. However, the physical considerations related to antenna arrangement have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%